Integration of ICT at Secondary Level School - Diyal, Suresh Bahadur; Pandey, Romkant (Innovative Research Journal, 2022)
This paper emphasizes the analysis of the Integration of Information and Communication Technology (ICT) at Secondary Level Schools in Kathmandu. This study explored the teacher's opinions about the Integration of ICT, and the situation of ICT tools in schools, explored the practices for ICT education in the Kathmandu district and find the challenges for Integrating ICT in education. This research used a quantitative method and the data was collected from a questionnaire. The results indicate that teachers think that ICT has great potential for enhancing collaborative activities among students and for developing highly relevant generic skills. However, also aware of the difficulties that both students and teachers face in educational practice. The study findings are useful for educators intending to integrate ICT tools in their lessons to better engage students in active learning. it helps to forward-thinking researchers, educators, and designers find innovative solutions and practical ideas for addressing the challenges and capitalizing on the visions of ICT and integration of ICT at the secondary level of school and in the field of education.